Role of Toxin Produced by Alternaria alternata in Leaf Blight of Anthurium and Its Detoxification by Antagonists - , S. Thangeswari, M. Deivamani, M. Paramasivam, K. Govindan, S. Malathi, V.K. Satya, R. Ramjegathesh, K. Sasikumar (Archives of Current Research International, 2024)
A study was conducted to investigate the degradation of the phytotoxin produced by the anthurium leaf blight pathogen Alternaria alternata (Fr.) Keissler by antagonistic bacterial and fungal strains. Toxin extracted from leaf blight pathogen caused by A. Alternata showed the typical symptoms of detached leaves and increased the loss of electrolytes from anthurium leaves. Among the biocontrol agents tested, Pseudomonas fluorescens strain CFP1 was found to be highly effective detoxification of the pathogen toxin by utilizing the carbon source.